(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article examines the organizational and legal basis of the prosecutor’s supervision over the implementation of legislation in the field of land in the Republic of Uzbekistan, the prevention of plundering of agricultural land, the role of the prosecutor’s supervision in the use of land plots, and other issues.